PERTUMBUHAN AKAR TANAMAN KARET PADA TANAH BEKAS TAMBANG BAUKSIT DENGAN APLIKASI BAHAN ORGANIK - Firdaus LN; Sri Wulandari; Giska Dwi Mulyeni (Program Studi Pendidikan Biologi, 2013)
The ex-situ experimental research on root growth of rubber (Hevea brasiliensis Mull. Arg. clone PB 260) cultivated in ex-mining bauxite soil byapplication of organic manure has been carried out at Natural Biology Education Laboratory University of Riau during January to June 2013. The purpose of this research was looked for a kind and mixture organic manure ratio to the ex -mining bauxite soil that gave the best root growth. The chicken and cow manure were used as source of organic matter in this single faktor experiment. Three ratios of organic manure : ex-mining bauxite soil (w/w) has been applied i.e control (exmining bauxite soil only), (1:1), and (1:2) were arranged according to Complete Randomize Design. The parameters that observed were root volume, wet weight of root, dry weight of root, shoot : root ratio. The data were analyzed by using one-way ANOVA and advance test by using Duncan Multiple Range Test (DMRT) in level of 5%. The results show that the mixture ratio 1:2 of cow organic manure and ex-mining bauxite soil gave the best root growth of rubber clone PB 260, particularly root volume (24,8 cm3), wet weight of root (24,2 g), dry weight of root (5,6 g) and shoot : root ratio (19,1 g). In conclusion, the mixture ratio 1:2 of cow manure and ex-mining bauxite is recommended for reclaiming bauxite ex-mining land by planting rubber plant PB 260 in term of root growth.Keywords : chicken and cow organic manure, ex-mining bauxite soil, Hevea brasiliensis Mull. Arg. clone PB 260, root growth